Surgical Outcomes of Third Ventriculostomy in Patients of Obstructive Hydrocephalus - Sohaib Ali, Tauseef Ullah, Muhammad Ibrahim Afridi, Tabraiz Wali Shah, Shafiq Ur Rehman, Hanif Ur Rahman, Idris Khan, Muhammad Taimur Khan, Ehsan Sayyed, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hydrocephalus is the accumulation of excess cerebrospinal fluid (CSF) in the ventricular system of the brain. Objectives: The main objective of this study is to find the surgical outcomes of third ventriculostomy in patients of obstructive hydrocephalus. Material and methods: The data was collected through non-probability consecutive sampling technique. There were 60 patients which were included in the study. A flexible endoscopic telecamera and a Bugbee electrocautery wire and monitor were used for the procedure. The main causes of hydrocephalus have been identified. history of meningitis, ventriculitis, or illness prior to the development of hydrocephalus; x-rays indicating separation or septa within the ventricles; or postoperative residue of hemosiderin or the presence of yellowish deposits were all taken into consideration of post infectious hydrocephalus. Results: There were 49 male and 11 female patients. The mean age of the patients was 39.38 ± 11.2 years. 27 (45%) patients had hydrocephalus due to tumors, 21 (35%) patients had aqueductal stenosis while 12 (20%) patients had benign cysts. Intraoperative bleeding occurred in 24 patients. ETV was successful in 54/60 – 90percent of the patients. A CSF leak was recognised in 09 patients. 07 patient developed a transient gaze palsy which had resolved when he came for his follow up visit on 10th post operative day. Practical implication: Use effective method for treatment of hydrocephalus in hospitals Conclusion: It is concluded that endoscopic third ventriculostomy, in general, is a very effective method of treatment for hydrocephalus. Keywords: Obstructive Hydrocephalus, ETV, Outcome, CSF, Brain, Ventricular